Pengujian Pengaruh Kepemilikan Institusional dan Ukuran Dewan Direksi Terhadap Penghindaran Pajak: Profitabilitas Sebagai Pemoderasi - Adityaputra, Stephanus Andi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Indonesia's Tax Ratio for the last 5 years (2019-2023) is still below 11% due to the low level of tax compliance, one of which is caused by the high practice of tax avoidance. Institutions as shareholders of the company and the board of directors as a component of corporate governance play an important role in tax avoidance practices. This study aims to examine the effect of institutional ownership and the size of the board of directors on tax avoidance moderated by profitability. Through the purposive sampling method, 68 research samples were obtained from coal sub-sector mining companies listed on the Indonesia Stock Exchange from 2021 to 2023. The research methods used are descriptive statistical analysis, classical assumption testing, simple linear regression, and Moderated Regression Analysis. The conclusion of the results of this study is that the coefficient value of institutional ownership in its influence on tax avoidance is -0.244 with a significance value of 0.084 (greater than 0.05) so that institutional ownership has a negative but insignificant effect on tax avoidance, while the coefficient value of the size of the board of directors in its influence on tax avoidance is 0.032 with a significance value of 0.025 (lower than 0.05) so that the size of the board of directors has a positive and significant effect on tax avoidance. The significance value of the interaction between institutional ownership and profitability is 0.114 (greater than 0.05) and the interaction value of the interaction between the size of the board of directors and profitability is 0.620 (greater than 0.05) indicating that profitability is unable to moderate the effect between institutional ownership and the size of the board of directors on tax avoidance.